1992
DOI: 10.1104/pp.99.3.1124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Kinetics and Reciprocal Inhibition of Nitrate and Nitrite Uptake in Roots of Uninduced and Induced Barley (Hordeum vulgare L.) Seedlings

Abstract: Nitrate and N02-transport by roots of 8-day-old uninduced and induced intact barley (Hordeum vulgare L. var CM 72) seedlings were compared to kinetic patterns, reciprocal inhibition of the transport systems, and the effect of the inhibitor, p-hydroxymercuribenzoate. Net uptake of N03-and N02-was measured by following the depletion of the ions from the uptake solutions. The roots of uninduced seedlings possessed a low concentration, saturable, low Km. possibly a constitutive uptake system, and a linear system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
94
2
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 27 publications
19
94
2
5
Order By: Relevance
“…This model conformed best with the measured data with regard to the obtained standard errors (data not shown) and the fitting of curves to the means of uptake rates (Fig. 3) Aslam et al 1992), but lower than those found in maize (24 mmol m -3 , Hole et al 1990), in wheat (27 mmol m -3 , Goyal & Huffaker 1986b) and in Arabidopsis (40 mmol m -3 , Doddema & Telkamp 1979) or in excised barley roots in earlier reports (110 mmol m -3 , Rao & Rains 1976a). Similar agreements were found for the 13 N-NO 3 -influx (Lee & Drew 1986: 14 mmol m -3 ;Siddiqi et al 1990: between 30 and 79 mmol m -3 depending on the N status of the plants).…”
Section: Kinetic Parametersmentioning
confidence: 69%
See 4 more Smart Citations
“…This model conformed best with the measured data with regard to the obtained standard errors (data not shown) and the fitting of curves to the means of uptake rates (Fig. 3) Aslam et al 1992), but lower than those found in maize (24 mmol m -3 , Hole et al 1990), in wheat (27 mmol m -3 , Goyal & Huffaker 1986b) and in Arabidopsis (40 mmol m -3 , Doddema & Telkamp 1979) or in excised barley roots in earlier reports (110 mmol m -3 , Rao & Rains 1976a). Similar agreements were found for the 13 N-NO 3 -influx (Lee & Drew 1986: 14 mmol m -3 ;Siddiqi et al 1990: between 30 and 79 mmol m -3 depending on the N status of the plants).…”
Section: Kinetic Parametersmentioning
confidence: 69%
“…The HATS is described as a saturable system, whereas the nature of the LATS is still not clear. Doddema & Telkamp (1979) and Goyal & Huffaker (1986b) found a second saturable system, but Siddiqi et al (1990) and Aslam, Travis & Huffaker (1992) observed a linear non-saturable component under higher concentrations of nitrate. Aslam et al (1992) even found two saturable, possibly constitutive systems in the low concentration range and a linear system at more than 500 mmol m -3 nitrate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations